Methyl Jasmonate-Treated Pepper (Capsicum annuum L.) Depresses Performance and Alters Activities of Protective, Detoxification and Digestive Enzymes of Green Peach Aphid [Myzus persicae (Sulzer) (Hemiptera: Aphididae)]. Issue 6 (21st December 2022) - Zhan, Xue; Liu, Ying; Liang, Xiao; Wu, Chunling; Liu, Xiaoqiang; Shui, Jun; Zhang, Yao; Wang, Ying; Chen, Qing
Abstract: Methyl jasmonate (MeJA) is a phytohormone that has been used to artificially induce plant resistance against multiple arthropod herbivores. However, it is still uncertain whether MeJA can trigger pepper plant resistance against Myzus persicae (Sulzer) (Hemiptera: Aphididae) (green peach aphid, GPA). In this study, we assessed the effects of different concentrations (0, 0.008, 0.04, 0.2, 1.0, and 5.0 mM) of MeJA-treated pepper on the development and reproduction performance of GPA to identify an appropriate concentration for vigorous resistance enhancement. MeJA dose was applied on the pepper to investigate the changes in activities of protective enzyme (superoxide dismutase, SOD; catalase, CAT; peroxidase, POD and polyphenol oxidase, PPO), detoxification enzymes (acetylcholinesterase, AchE; glutathione S-transferase, GSTs; cytocrome P450, CYP450, and carboxylesterase, CarE), and digestive enzymes (protease, PRO and amylase, AMY) in GPA. The results showed that all concentrations of MeJA-treated pepper significantly suppressed GPA performance, wherein 0.2 mM was the optimal concentration, as it presented the lowest intrinsic rate of increase ( r m ), finite rate of increase ( λ ), and the highest population doubling time ( Dt ) values. Furthermore, the protective enzymes (SOD and CAT), detoxification enzymes (GSTs, CYP450, and CarE), and AMY activities increased significantly in MeJA-treated groups than the control group, while the POD and PPO activities were remarkly inhibited under 0.2 mM treatment. These findings indicate that exogenous spraying of 0.2 mM of MeJA significantly enhanced pepper resistance against GPA. The result of this study suggests MeJA application can be used as a promising strategy in integrative management of this insect pest.